Integrating Neuroeconomic Insights into the Islamic Economic Decision-Making Model - Alfina Rahmatia; Arief Dwi Saputra (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract Neuroeconomics integrates economics, neuroscience, and psychology to offer empirical insights into human decision-making processes by linking neural activity with preference and risk assessment. Despite its rapid development in conventional economics, its synthesis with Islamic economic principles remains profoundly underexplored. This study aims to bridge this gap by mapping the global neuroeconomic research trends from 2004 to 2024 and integrating these empirical findings into an Islamic economic decision-making model. Employing a mixed-methods design, this study conducts a bibliometric analysis of 718 Scopus-indexed documents using VOSviewer and a sentiment analysis via NVivo 12, supplemented by an interpretive qualitative synthesis. The empirical findings reveal a fluctuating publication trend peaking in 2010, alongside a dominant narrative characterized by cautious skepticism regarding methodological boundaries. The qualitative integration demonstrates that neurobiological mechanisms governing bounded rationality, risk aversion, and prosocial reward systems strongly reinforce Islamic moral imperatives. Specifically, altruistic acts like Zakat activate neural reward pathways, validating the biological basis of maslahah (public interest). This study provides a novel conceptual framework that aligns frontline neuroscience with an ancient ethical system, offering policy implications for designing culturally congruent and socially responsible Islamic financial products. Abstrak Neuroekonomi mengintegrasikan ekonomi, ilmu saraf, dan psikologi untuk menawarkan wawasan empiris tentang proses pengambilan keputusan manusia dengan menghubungkan aktivitas saraf dengan preferensi dan penilaian risiko. Terlepas dari perkembangannya yang pesat dalam ekonomi konvensional, sintesisnya dengan prinsip-prinsip ekonomi Islam masih sangat kurang dieksplorasi. Studi ini bertujuan untuk menjembatani kesenjangan ini dengan memetakan tren penelitian neuroekonomi global dari tahun 2004 hingga 2024 dan mengintegrasikan temuan empiris ini ke dalam model pengambilan keputusan ekonomi Islam. Dengan menggunakan desain metode campuran, studi ini melakukan analisis bibliometrik terhadap 718 dokumen yang diindeks Scopus menggunakan VOSviewer dan analisis sentimen melalui NVivo 12, dilengkapi dengan sintesis kualitatif interpretatif. Temuan empiris mengungkapkan tren publikasi yang berfluktuasi yang mencapai puncaknya pada tahun 2010, bersamaan dengan narasi dominan yang dicirikan oleh skeptisisme yang hati-hati mengenai batasan metodologis. Integrasi kualitatif menunjukkan bahwa mekanisme neurobiologis yang mengatur rasionalitas terbatas, penghindaran risiko, dan sistem penghargaan prososial sangat memperkuat imperatif moral Islam. Secara khusus, tindakan altruistik seperti Zakat mengaktifkan jalur penghargaan saraf, memvalidasi dasar biologis Maslahah (kepentingan umum). Studi ini menyediakan kerangka konseptual baru yang menyelaraskan ilmu saraf terdepan dengan sistem etika kuno, menawarkan implikasi kebijakan untuk merancang produk keuangan Islam yang sesuai secara budaya dan bertanggung jawab secara sosial.